Analysis Between Knowledge And Attitude With Pembatasan Sosial Berskala Besar (PSBB) In DKI Jakarta - Arief C Nugraha; Muhammad Cholifihani (CV. Inara, 2021)
This study aims to prove and analyze the influence of knowledge and attitudes with the Pembatasan Sosial Berskala Besar (PSBB) in DKI Jakarta. This research uses survey method, quantitative research type with explanatory format. This research was conducted on people domiciled in DKI Jakarta, from April to July 2021. The research population was all people domiciled in DKI Jakarta. The research sample is 200 people who live in DKI Jakarta. The research trial consisted of 30 people living in DKI Jakarta outside the sample used in the study. The results showed that there was a positive and significant influence between knowledge and attitudes together with the PSBB policy in DKI Jakarta. The coefficient of determination is 0.342 or 34.2% through the regression model = 31.311 + 0.876X1 + 0.363X2. The contribution of the independent variable to the dependent variable was highest on knowledge with a value of beta (β) = 0.499; tcount = 7,462; and sig. = 0.000. Based on these findings, it can be concluded that if you want to improve the PSBB policy in DKI Jakarta, then factors such as knowledge and attitudes need to be improved together.